Le Panégyrique de S. Théophane le Confesseur par S. Théodore Stoudite (BHG 1792b) Édition critique du texte intégral - Efthymiadis, Stéphane (Analecta Bollandiana, 1993)
On the basis of codex Athos Lavra E 169, the Panegyric to Theophanes the Confessor by Theodore the Studite is now edited in full. This work was partly edited by C. Van de Vorst in AB 31 (1912), after a codex of Basel. The introduction touches upon the main historical points now brought in light and gives a brief analysis of Theodore's style and diction. The translation is followed by additional linguistic and historical commentary.